A narrativa de crimes de assassinatos cruéis : um estudo psicanalítico - Mai, Luanza Pavesi (2011)
This study aims to investigate the unconsciousness manifestations that may be present during the reading of books of heinous crimes of murder. Therefore, under the perspective of what is called acting out, the enigma emerged in this work corresponds to the relationship established among reader and some narratives of heinous crimes of murder, which has been mediated by writing. Accordingly to it, this research psychoanalytically debates the experience of a supposititious reader forward the reading of the following books: Serial Killers: made in Brasil" (Casoy, 2004), "Serial Killer Louco ou Cruel?" (Casoy, 2008) andfinally "O quinto mandamento: Caso de Polícia" (Casoy, 2009). This study is based on a bibliographic research, which answers what has been thought as work proposal. Thus, as main theoretical support, it is used Sigmund Freud's texts, essencially those referred to the author's creative process and literature as well. As important as, this work is also supported by André Green's studies, principally the ideas presented in "O desligamento" (1994) e "Narcisismo de vida, narcisismo de morte" (1995). As a conclusion, it is known that there is a common nucleus to this narratives, which is permeated by the wish fulfillment, that corresponds to a fantasy extent essentially linked to the following unconsciousness manifestations, allowed to reader: the originary scene, the beating fantasy, the double phenomenon, and, at long last, the Dead mother complex.